Pengaruh Fluktuasi Financial Leverage dan Operating Leverage Terhadap Profitabilitas - Banafza, Salfa; Metalia, Mega (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
This study aims to examine the effect of financial leverage and operating leverage on profitability in construction and property companies listed on the Indonesia Stock Exchange in 2018-2022. This research is a type of quantitative research using secondary data from the Indonesian Stock Exchange and the official websites of each company. The sampling method used purposive sampling and a sample of 22 companies was obtained with an observation period of 5 years so that the total research sample was 11 data. The data analysis technique used is multiple linear regression using SPSS 27 software. Based on the research results, it was found that financial leverage and operating leverage simultaneously influence profitability. Partially, financial leverage has a negative effect on profitability and operating leverage has a positive effect on profitability.